Identification, Evaluation, and Prioritization of Factors Affecting the Identification of Out-of-School Children in Primary Education: A Human Development Index Promotion Approach in Iran - Hoseinzadeh, Maryam; Poushaneh, Kambiz; Assareh, Alireza; Nobakht, Mohammad Bagher; Rezazadeh Bahadoran, Hamidreza (Assessment and Practice in Educational Sciences, 2024)
The present study was conducted with the aim of identifying, evaluating, and prioritizing the factors influencing the identification of out-of-school children in primary education, with a focus on enhancing the Human Development Index in Iran. In terms of objective, the study is applied; in terms of data type, it is a sequential mixed-methods study with an exploratory approach; in terms of paradigm, it follows a pragmatic orientation; and in terms of nature, the qualitative part involves qualitative content analysis with a thematic analysis approach, while the quantitative part is descriptive-analytical and survey/correlational in type. The study population in the qualitative phase consisted of theoretical experts (faculty members in the field of educational sciences) and practical experts (relevant officials from the Ministry of Education). Based on the principle of data saturation and purposive sampling, 15 interviewees were selected. In the quantitative phase, the statistical population included all staff from the Deputy for Primary Education and the Deputy for Cultural and Educational Affairs. Using the minimum sample size formula for confirmatory factor analysis and a combined (multi-stage) sampling method, 242 employees were selected. Data collection methods included semi-structured interviews in the qualitative phase and researcher-developed questionnaires in the quantitative phase. The validity and reliability of the instruments were examined and confirmed in both phases. Data analysis methods included thematic analysis using Maxqda-V18 in the qualitative phase and descriptive and statistical analysis (confirmatory factor analysis) using SPSS-V27 and SmartPLS-V3 in the quantitative phase. The findings revealed that the dimensions of identifying out-of-school children in primary education with a Human Development Index promotion approach include social, economic, and educational dimensions. The results also showed that the economic dimension was the top priority, while the social dimension was ranked last.